2022
DOI: 10.1155/2022/7996754
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Dexamethasone versus Dexmedetomidine Combined with Local Anaesthetics in Brachial Plexus Block: A Meta-Analysis and Systematic Review

Abstract: Background. Both dexamethasone and dexmedetomidine are commonly used local anaesthetic adjuvants in brachial plexus block to enhance the blocking effect. However, it is unclear which of the two drugs is more effective in a brachial plexus block. This article compares the effects of dexamethasone and dexmedetomidine combined with local anaesthetics in brachial plexus block through meta-analysis, availing information for current practice and future research. Methods. We conducted a search of the PubMed, Embase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In terms of the adverse effects, a fall in heart rate and mean arterial pressure was noticed more commonly in the dexmedetomidine group in our study, as well as those of other studies (p = 0.006 [20] and p = 0.001 [19]). Dexmedetomidine also resulted in an increased level of sedation postoperatively, as was also found by other studies [18,19].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In terms of the adverse effects, a fall in heart rate and mean arterial pressure was noticed more commonly in the dexmedetomidine group in our study, as well as those of other studies (p = 0.006 [20] and p = 0.001 [19]). Dexmedetomidine also resulted in an increased level of sedation postoperatively, as was also found by other studies [18,19].…”
Section: Discussionsupporting
confidence: 85%
“…Both adjuvants have previously undergone extensive research [ 15 - 17 ]. However, the supraclavicular technique has been used in the majority of these trials to block the brachial plexus [ 18 ]. We found that adding 6 mg of dexamethasone as an adjuvant to 25 mL of 0.5% bupivacaine produced sensory and motor blocks that lasted noticeably longer than 75 mcg of dexmedetomidine, postoperative analgesia, and delayed time for the first rescue analgesic without causing unneeded adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Steroids act by reducing the local inflammation triggered by mechanical, immunological, or chemical factors. [ 13 ] Corticosteroids inhibit phospholipase A2, deactivating a proinflammatory cascade. [ 10 ] In addition, it has been reported that local CS may block type-C sensory nerve fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%